THE INFLUENCE OF INFORMATICS LEARNING FACILITIES AND INFRASTRUCTURE ON STUDENTS' ABILITY TO OPERATE COMPUTERS AT AL-ISHLAH MIDDLE SCHOOL, CILEGON - Reza Novanty; Beni Junedi; Ade Fricticarani (Cakrawala Pedagogik, 2025)
This study was motivated by the limited informatics learning facilities and infrastructure at Al-Ishlah Middle School, Cilegon. Observations revealed several problems in Informatics learning, including inadequate facilities and the suboptimal use of learning media. This research aimed to examine the influence of informatics learning facilities and infrastructure on students’ ability to operate computers. The study employed a quantitative method based on the philosophy of positivism to test hypotheses. This method is considered scientific because it reflects principles of concreteness, objectivity, measurability, rationality, and systematic inquiry. The research analyzed the management and utilization of computer laboratory facilities through quantitative data. Reliability testing showed that the facilities and infrastructure variable had a coefficient of 0.815, while the student ability variable had a coefficient of 0.913 from 60 statement items. Questionnaires X and Y, each with 30 items, were tested for validity and reliability. Data from 44 respondents showed average scores of 92.14 and 78.30, both normally distributed. A significance value of 0.396 indicated that the alternative hypothesis (Ha) was accepted. The results concluded that informatics learning facilities and infrastructure significantly affect students’ ability to operate computers. The quality of these facilities is positively correlated with student competence. Although the average student ability score reached 78.30, improvements are still needed. Therefore, continuous efforts to enhance the quality of facilities, infrastructure, and informatics training are essential to optimize students’ learning outcomes.